Weight gain, body image and sexual function in young patients treated with contraceptive vaginal ring. A prospective pilot study. (3rd August 2017) - Morotti, Elena; Casadio, Paolo; Guasina, Francesca; Battaglia, Bruno; Mattioli, Mara; Battaglia, Cesare
Abstract: Introduction: Oral contraceptives could induce mood changes. As far as our knowledge, there are no studies in literature that have examined the role of vaginal contraception in self-perceived body image. Aim : To evaluate the effects of intravaginal contraception on weight gain and perceived body image in relation with the Beck's Depression Inventory questionnaire (BDI) and the McCoy Female Sexuality Questionnaire (MFSQ). Methods : Twenty-one adult (18–35 years old) eumenorrheic (menstrual cycle of 25–35 days), lean (body mass index – BMI – of 19–25 kg/m 2 ) women who were referred for hormonal contraception were administered the Stunkard Figure Rating Scale (FRS), BDI and MFSQ. Subjects were studied in basal condition and after 6 months of therapy with vaginal contraception (NuvaRing®; Organon-Schering-Plough Italia, Milan, Italy). Main outcome measures : BMI, FRS, MFSQ and BDI. Results : After 6 months of therapy with NuvaRing®, both body weight (60.0 ± 8.3; p  = 0.050) and BMI (22.1 ± 3.1; p  = 0.028) slightly, but statistically, increased. FRS and BDI showed no differences after the vaginal contraception. Hormonal contraception was associated with a significant decrease in the two-factor Italian MFSQ score. Conclusions : Vaginal ring seems a good alternative to other hormonal contraceptive not significantly altering the female sexuality and not influencing the FRS and BDI.